Pelatihan Pembuatan Branding IGPAUDMNU Melalui Optimalisasi Instagram - pratama, firman hadi sukma; Nia Saurina; Lestari Retnawati; Nonot Wisnu Karyanto; Noven Indra Prasetya; Udik Pudjianto (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
Branding is the definition and development of identity for a brand includingcharacter, content, and relationship with consumers in any type ofcommunication or interaction. Institutional branding is the identity of aninstitution that can create a perception in the minds of readers, namelyregarding the values ​​and qualities held by the owner of the name. Branding ofan institution is also a way to shape self-image, personal character, areas ofexpertise and interest as well as special things for the community with the aimof forming positive perceptions. In the personal branding process, self-imagecan be formed when uploading photos and videos on Instagram.IGPAUDMNU is an association of Early Childhood Education Teachers underthe auspices of the Muslimat Nadhalatul Ulama whose members are teachersthroughout East Java Province. The aim of this community service activity isInstagram training to improve Institutional Branding for IGPAUDMNU EastJava Province using Instagram.The implementation method in community service uses qualitative methodswhich include delivering material, collecting data by interviews. Thedescription of the material starts from motivation about technology to lateroperation and optimization of the application. Data collection was carried outby interviews and taking documentation through pictures of each social mediaowned by Wijaya Kusuma University Surabaya with the ukwsmediacenter igaccount.Community service activities can provide benefits for teachers in terms ofinformation services, communication and documentation facilities for everyactivity carried out by young children as students of the participants which canbe seen by the entire community. Teachers can understand how to use socialmedia as a means of communication, information and documentation.Keywords: institutional branding, Instagram, IGPAUDMNU